Raisina model : Indian democracy at 70 - Meghnad Desai (Gurgaon Penguin Books, 2018)
Meghnad Desai reflects on Indian democracy as it completes seventy years of colourful, eventful and energetic parliamentary existence. Pulling no punches, Desai looks at the history and evolution of Indian democratic institutions, pinpointing their achievements, but also their repeated failure to live up to the standards envisaged by the nation's founders. Drawing on his own career as a Labour peer in Britain's House of Lords, Desai has the rare understanding and familiarity with the process of politics, and is able therefore to identify its universal features and zoom in on its uniquely Indian aspects. This is a candid, reflective and unsparing view of the precepts and practice of Indian politics. It traces at the evolution and growth of identity politics, coalition governments and single-party rule and the differing political narratives of the north and the south. The Raisina Model is a critical and frequently uncomfortable meditation on India's contemporary political culture.
Keywords: Democracy; Political Science